(untitled) (Research, Society and Development, 2021)
With the social distancing required by the coronavirus (COVID-19) pandemic, the creation of a new pedagogical model became a sudden challenge for educational institutions. This study sought to assess health science professors’ experiences and perceptions during the COVID-19 pandemic. An epidemiological, descriptive, cross-sectional, observational, and quantitative approach was applied and included the application of a structured and self-administered virtual questionnaire containing objective and multiple-choice questions on demographic data, online teaching activities, continuing education, learning environments, and difficulties faced. Seven questions from the Generalized Anxiety Disorder Screening Tool (GAD-7) were added to assess anxiety. One hundred and thirty-eight university professors in Brazil completed the questionnaire. Of these, 87 were employed by public institutions and 51 worked at private institutions. Geopolitical region in the country and university funding type were associated with universities’ ability or decision to offer courses online. Among the professors, being of female gender and a decrease in household income were the factors most closely associated with increased anxiety. Professors also reported difficulties in interacting with students online, the need to assume more childcare, and difficulty in concentrating at home to be the main barriers to successful online teaching.